RAILWAY AND PORTS INTEGRATION SYSTEM AS SOLUTION OF ISLAND TRANSPORTATION PROBLEM (CASE STUDY SUMATRA ISLAND) - Satrio Teguh Amandiri; Ahmadi Ahmadi; Budi Santoso W (JOURNAL ASRO, 2018)
ABSTRACT The quality of Transportation system is one of island economic level determinant. Railway transportation evidently more efficient than road transportation. Trans-Sumatra railway construction can be a solution for transportation problem in Sumatra Island. This analysis integrated railway and port to improve economic development in 8 provinces on Sumatra using Spanning Tree and Dijkstra algorithm. It need 1965 kilometers of railway to connect all the 8 provinces. It also generates 1518 kilometers as the distance of Malahayati Port to Panjang Port connection. This integrated system can be a breakthrough solution for Sumatra transportation problem in economic development and the Malacca Strait traffic problem. Keywords: Trans-Sumatra railway, Minimum Route, Spanning Tree Algorithm, Dijkstra, Algorithm